Non-immune hidrops fetalis: Apropos of a case - CÁRDENAS, JOEL (2004)
We present a case of non-immune hydrops fetalis diagnosed by antenatal ultrasound at 31 weeks of gestation . Fetal karyotyping of blood sample obtained by cordocentesis was abnormal. The fetus died 6 days later. Postmortem examination was compatible with Down syndrome. We report the possibility of antenatal hydrops fetalis diagnosis by invasive techniques.